A descriptive study of career paths of dentists in Paranaque class 1988-1995 - Abesamis, Zarah R.; Frange, Melanie Ruth Karganilla (Adviser).
A study was done among dentists of Paranaque belonging to Classes 1988-1995. The study was undertaken to determine the career paths of dentists in Paranaque from their time of graduation to the present year and the influencing factors behind the chosen careers. The study was intended to identify the career options a newly graduated dentist has and the careers actually chosen by dentists. Seventy-one licensed dentists who are currently members of the Paranaque Dental Society, were included in the study. Questionnaires were sent through mail and/or personally given to the said subjects. Statistical analysis of the data obtained revealed that after graduation, 80.28% of graduates immediately went into private practice. Also, most of the dentists who went into private practice opted for associateship, particularly during their first years in practice. The most motivating factors in the choice of initial careers were the need for experience and the lack of financial resources, lack of confidence and the need for immediate compensation. Of dentists who had changes in their careers, more subjects shifted to solo practice rather than other types of practice with reasons of low productivity, insufficient income in their initial practice and the desire to work alone.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.